Hubungan Kecenderungan Social Media Addiction dengan Empati pada Remaja di Surabaya - Kurniaputri, Yenni; Adhyatma, Made Dharmawan Rama (Psychopreneur Journal, 2021)
Adolescent is impotant to build a teenager’s personality, because their social-emotional-physical development starts and ends at adolescent phase. One of the important factor that can build teenager is empathy. Empathy is a response of understanding feelings and know the reason behind the feelings, empathy consists of affective and cognitive component. Right now, empathy on teenagers is stunted because of social media that can influence them into having low empathy, seeing news that’s full with hoax and teenage violence. This study’s purpose is to know the correlation between social media addiction tendency and empathy on teenagers in Surabaya. The participants were chosen using purposive sampling technique. The normality test was not fulfilled, so researcher use non-parametric statistical technique (Kendall’s Tau-b). The result shows significancy score = 0,000 (p < 0.05) and correlation score (r) = 0,106. With that, it can be concluded that there is a positive correlation between social media addiction tendency and empathy on teenagers in Surabaya.